(untitled) (New Agenda: SA Journal of Social and Economic Policy, 2024)
An awful lot has changed during South Africa’s 30 years of democracy – but clearly not nearly enough. The state’s provision of certain basic services is broadly recognised, and commended, but democracy is not measured according to the ability of the state to deliver services to its citizens. It is reflected in the ability of every person to exercise their human rights to secure better lives for themselves, their families and their communities. Manifesto’s aside, how could the country now move forward, from where we are? We publish three views – from the Cape Town-based Progressive Citizens Initiative, from Abahlali baseMjondolo and from My Vote Counts.